Unveiling the Link Between Low Testosterone and Worsening Heart Failure Symptoms: A Literature Review - Ryan Ardiansyah; Akhmad Sandy Sauqy (Sumatera Medical Journal, 2025)
Background: Heart failure can result from a variety of factors, including hypertension, coronary artery disease, diabetes, obesity, smoking, and genetic predispositions. Research indicates that testosterone levels are markedly lower in patients with heart failure compared to healthy individuals, suggesting that low testosterone may play a role in the onset or progression of heart failure. Objective: This review endeavors to examine the impact of low testosterone levels on the clinical manifestations of heart failure patients. Methods: A literature review was conducted across three databases, Google Scholar, PubMed, and Science Direct, employing the keywords "testosterone" and "heart failure." The search was further refined through specific inclusion and exclusion criteria, culminating in data from eight international journals. Results: Testosterone deficiency was associated with deteriorated outcomes in men diagnosed with HFpEF, with lower testosterone levels corresponding to more severe symptoms and diminished quality of life. It influences myocardial contractility, energy metabolism, apoptosis, and cardiac remodeling processes. Conclusion: Men suffering from heart failure with concomitant low testosterone levels are generally observed to have increased mortality rates and less favorable prognoses.